PERAN MANAJEMEN KEWIRAUSAHAAN DAN TEKNOLOGI INFORMASI PADA SISWA SMK HANG NADIM BATAM: The Role of Entrepreneurship and Information Technology Management in Hang Nadim Batam Vocational School Students - Mauli Siagian; Wasiman Wasiman; Koko Handoko; Pastima Simanjuntak (PUAN INDONESIA, 2023)
The implementation of community service carried out at Hang Nadim Batam Vocational School aims to provide knowledge to students to be able to know and understand about entrepreneurship management which includes business planning, business opportunities, products or services that will be used as a business and implementation in implementing the business in public. Creating students to get used to using digital platform applications such as WhatsApp, Shopee, Lasada and so on, this aims to help businesses in terms of effective and efficient promotions. The methods used in community service are lectures, training and discussions. This is also done so that service participants don't get bored. The result of the service is that students know and understand about entrepreneurial management such as planning, implementation in business and bookkeeping in business, so that this is important for students to know as a provision in the community after graduating from school and getting involved in the community.